Pengaruh Disiplin Kerja dan Stres Kerja terhadap Motivasi Serta Dampaknya pada Kinerja Pegawai Perumda Air Minum Tirta Merangin - Hardian, Riki; Suryani, Arna; Yamali, Fakhrul Rozi (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to describe the discipline, work stress, motivation and performance of PERUMDA Tirta Merangin employees and to analyze the effect of partial and simultaneous work discipline and stress directly and indirectly on work motivation and employee performance, as well as to analyze work motivation on employee performance. To answer the purpose of this research, this research is supported by theoretical studies related to research variables, namely work discipline, work stress, work motivation and performance. In addition, the author is also looking for relevant previous research in the form of articles/journals and previous theses to support this research. From the path analysis test conducted, it was found that work discipline and stress affected work motivation by 46.28% while the rest was influenced by other variants. Work discipline and work stress affect 43.14% of employee performance at PERUMDA Tirta Merangin. This study concluded work discipline, work stress, work motivation and employee performance in good and high condition. In addition, work discipline and work stress partially and simultaneously have a positive and significant influence on work motivation and employee performance at PERUMDA Tirta Merangin. Similarly, work motivation has a positive and significant influence on employee performance.